Identifying the Gaps in the Management of Work Integrated Learning Among TVET College National Certificate (Vocational) Students (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2024)
Work Integrated Learning (WIL) is a crucial activity for students enrolled in Technical and Vocational Education and Training (TVET) programs in South Africa and globally. Effective management of this activity is essential to ensure that students are well-prepared for their placement in the workplace. Unfortunately, the current situation in South African TVET colleges often falls short, with students frequently finding themselves in workplaces where they lack the necessary readiness. To address this issue, a mixed-method approach was employed to select 50 Level 4 students from the National Certificate Vocational program and four Work Integrated Learning (WIL) coordinators. The objective was to identify the challenges faced by students during their WIL experience. Data was collected through questionnaires administered to the students and face-to-face interviews conducted with the WIL coordinators. The findings of the study revealed that 68% of the students were not adequately informed about workplace dynamics, which posed a significant challenge. Additionally, 82% of the respondents stated that they were never briefed on the employer's expectations upon their arrival at the workplace. While students found the activities in the workplace interesting, they observed a noticeable gap between what they learned in college and the realities of the industry. These challenges clearly indicate a lack of proper WIL management in the TVET colleges. To address these issues, it is recommended that the college curriculum planner collaborates closely with industries to align the curriculum with industry expectations and requirements. This synergy will enhance students' WIL experience and better prepare them for the workplace.